PSIKODIAGNOSTIK PERMASALAHAN ANAK USIA DINI - Mashar, Riana (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2010)
Early childhood as a golden period of development of the child should be supported with the provision of appropriate stimulation. In the world of education, psikodiagnostik as a method to assess the presence of abnormalities in a psychic to help facilitate an overview of strengths and weaknesses of individuals, in various aspects of both cognitive, physical, emotional, trend, personality, talents, interests, and various other aspects, so that educators can better provide appropriate stimulation for the optimization of the development of the child. There are five main methods in psikodiagnostik early childhood, ie interviews, observation, home visit, the test is structured, and unstructured tests.